Menggali Nilai Perlindungan Anak dalam Karya Klasik untuk Pengembangan Pendidikan Modern yang Inklusif - Ardiansah, Yoga; Hasaniyah, Nur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
Child protection is an integral part of educational efforts to ensure the fulfillment of children's rights and the sustainability of national development. In the context of educational sciences, the values of child protection can be found in classical works, such as  Ihya’ ‘Ulum al-Din  by Imam al-Ghazali, which highlights the importance of parental and educator responsibility in shaping children's character through moral, spiritual, and social education. This article examines the relevance of child protection concepts in classical literature to modern educational policies. This study employs a qualitative approach with a text analysis method. The focus of the research is on exploring the content of  Ihya’ ‘Ulum al-Din  by Imam al-Ghazali, with an emphasis on child protection values relevant to education. A qualitative approach was chosen as it is well-suited for uncovering the deeper meanings of moral and spiritual concepts within classical texts. The findings indicate that the principles of justice ( al-‘adalah ), compassion ( al-rahmah ), and safeguarding trust ( hifz al-amanah ) emphasized in classical literature can support the development of inclusive and holistic education systems in the contemporary era. The synergy between traditional values and modern approaches is deemed capable of strengthening child protection in various aspects of education. By integrating the traditional values taught by al-Ghazali into the modern education system, it is hoped that a synergy can be created to support more comprehensive child protection. This synergy allows the education system to focus not only on academic achievement but also on the holistic development of children's character. Therefore, reviving these values becomes a strategic step toward fostering a more humane and sustainable education.